Diversity and distribution of Actinobacteria associated with reef coral Porites lutea - Kuang, Weiqi; Li, Jie; Zhang, Si; Long, Lijuan (Frontiers in Microbiology, 2015)
Actinobacteria is a ubiquitous major group in coral holobiont. The diversity and spatial and temporal distribution of actinobacteria have been rarely documented. In this study, diversity of actinobacteria associated with mucus, tissue and skeleton of Porites lutea and in the surrounding seawater were examined every three months for 1 year on Luhuitou fringing reef. The population structures of the P. lutea-associated actinobacteria were analyzed using phylogenetic analysis of 16S rRNA gene clone libraries, which demonstrated highly diverse actinobacteria profiles in P. lutea. A total of twenty-five described families and ten unnamed families were determined in the populations, and 12 genera were firstly detected in corals. The Actinobacteria diversity was significantly different between the P. lutea and the surrounding seawater. Only 10 OTUs were shared by the seawater and coral samples. Redundancy and hierarchical cluster analyses were performed to analyze the correlation between the variations of actinobacteria population within the divergent compartments of P. lutea, seasonal changes, and environmental factors. The actinobacteria communities in the same coral compartment tended to cluster together. Even so, an extremely small fraction of OTUs was common in all three P. lutea compartments. Analysis of the relationship between actinobacteria assemblages and the environmental parameters showed that several genera were closely related to specific environmental factors. This study highlights that coral-associated actinobacteria populations are highly diverse, and spatially structured within P. lutea, and they are distinct from which in the ambient seawater.